Laboratory Study for Biodegradation of Oxymatrine Insecticide by Single and Mixed Cultures of Fungi Isolated from Agriculture Soils in Basrah Governorate, Iraq (Baghdad Science Journal, 2019)
This study focuses on the biodegradation of oxymatrine insecticide by some soil fungi isolated from four agriculture stations. The results showed that the highest degradation rate 94.66% was recorded by Ulocladium sp. at 10 days and A. niger recorded the lowest degradation rate 45.86%, while at 20 days Ulocladium sp. also showed the highest degradation rate 94.98% and the lowest degradation rate reached to 82.49% with A.niger. The mix (Exerohilum sp.+Ulocladium sp.) recorded the highest degradation rate of oxymatrine insecticide 90.22%, 88.51%, 85.34% at 4, 8 and 12 ppm.The use of mixed isolates enhanced the biodegradation process. There is no study of oxymatrine biodegradation so this study is the first of its kind in the region which can be used as a baseline study for incoming studies